KARAKTERISTIK KEPEMIMPINAN TRANSFORMASIONAL DI LEMBAGA PENDIDIKAN ISLAM - Samsudin Samsudin IAI Sunan Giri Ponorogo; Suci Midsyahri Azizah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
The characteristics of transformational leadership play a very strategic role in determining the progress and setbacks of an educational institution. Educational institutions need a leader figure to advance, develop and bring the institution they lead to a better direction. Transformational leadership is a modern leadership style that is able to change from vision and mission to action and is done by making a clear vision, motivating staff to be creative, innovative, building a learning culture, and building effective communication. The characteristics of transformational leadership become the basis for how a leader should behave and act on his members. The characteristics of transformational leadership include: Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration. It seems that these characteristics are in line with the leadership of the Indonesian education figure, Ki Hajar Dewantoro, known by the motto